Aeroelastic assessment of cracked composite plate by means of fully coupled finite element and Doublet Lattice Method - Abdullah, Nur Azam; Curiel-Sosa, Jose Luis; Akbar, Mahesa (Elsevier, 2018)
This paper presents an investigation on flutter speed of cracked composite plates. This work is divided into two sections: (a) variation of crack length at a fixed location on the plate, and (b) variation of crack location on the plate with a fixed crack length, modelled as a unidirectional composite for 00,900 and 1350 orientations. Mori- Tanaka homogenization model is applied to obtain the effective composite constitutive properties as the function of fiber and matrix volume fraction. Doublet Lattice Method (DLM) is used to calculate the unsteady aerodynamic forces, i.e., lift distributions. It is found that the existence of small crack ratio on the composite plate (less than 0.4) has triggered an increment of the flutter speed. To support this statement, flutter response modes for each crack ratio are plotted, where the structure appears to be more stiffened than the undamaged plate. However, the crack results in the reduction of flutter speed when the crack ratio reaches 0.5. For the crack location assessment, the flutter speed increases as the crack location moves from the root to the tip due to the reduction of flutter frequency. The results show a good agreement with the validation using Strip Theory considering unsteady aerodynamics.